(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: The purpose of the article is to explore the concept of "carpe diem" in English literature, specifically focusing on its usage in poetry. The article discusses the meaning and origin of the Latin phrase "carpe diem," also references various literary works that employ the theme of carpe diem, such as the poems “The Flea” by John Donne and ‘To His Coy Mistress’ by Andrew Marvell.